Multiple Relationship And The Roles Of Institutional Investors: The Islamic Perspective - Nurul Aini Muhamed; Nathasa Mazna Ramli; Haslinda Yusof (Islami Bank Training and Research Academy (IBTRA), 2024)
The role of firms towards fulfilling needs and demands of stakeholdersbecomes the landmark of the Stakeholder Theory. Profit maximization under the monetary rewards should notbecome the main objective of the firms. The idea is contradictory from what has been detailed earlier in the well-known Agency Theory that assumes the obligation of firmis to maximize shareholders’ wealth. These two positions brought up the main contradictive idea within the conventional perspective of firms. With regards to this concern, the paper focuses on tiers of relationship of three main parties, i.e stakeholders of institutional investors, institutional investors and investee companies. Specifically, it aims to identify the roles of institutional investors from Islamic foundation, taking consideration on their position as the intermediaries between their own stakeholders and investee companies. The focus on institutional investors and their outstanding roles in the present context will be clarified from the contractual obligation under the Islamic framework, and this will be extended beyond the discussion in the Agency Theory and Stakeholder Theory. This paper theoretically explores and proposes the role of institutional investors in business environment in the way to manifest their responsibility towards stakeholdersfrom the Islamic framework.